1982
DOI: 10.2172/5303977
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of synfuel spill cleanup options

Abstract: Production of synthetic fuels will increase in the next two decades due to competitive economics and the world market for petroleum derived fuels. Increasing demand for synfuels has resulted in the need to determine the impact that synfuels production may exert on the environment. In particular, the goal of this program is to determine how to mitigate spills of synfuels and synfuel intermediaries. This chapter estimates synfuels production through the year 2000, and identifies, based on case histories, the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Currently available gelators are not commercially relevant, rendered impractical due to toxicity of formulations, large dose requirements, cumbersome deployment methods, and high costs . Recently, a renewed interest in gelators has led researchers to begin developing new chemistries to overcome some of the challenges mentioned above. , Both Mukherjee and Mukhopadhyay and Vibhute et al independently reported environmentally friendly, carbohydrate-based gelators capable of selectively gelling organic liquids and oils in organic–aqueous mixtures at low doses.…”
Section: Introductionmentioning
confidence: 99%
“…Currently available gelators are not commercially relevant, rendered impractical due to toxicity of formulations, large dose requirements, cumbersome deployment methods, and high costs . Recently, a renewed interest in gelators has led researchers to begin developing new chemistries to overcome some of the challenges mentioned above. , Both Mukherjee and Mukhopadhyay and Vibhute et al independently reported environmentally friendly, carbohydrate-based gelators capable of selectively gelling organic liquids and oils in organic–aqueous mixtures at low doses.…”
Section: Introductionmentioning
confidence: 99%